Introducing Versioning-Based Software Online Upgrade Framework over a Peer-to-Peer Network - Ma, Kun; Abraham, Ajith (Computing and Informatics, 2016)
Speed and trend in the software evolution demand the more flexible and available software. For the large-scale software, the availability and automation of current software online upgrade approach is not ideal, which brings the managers much work to maintain all the versions of software. In this paper, we introduce the versioning-based software online upgrade framework (VSOUF) over BitTorrent-like Peer-to-Peer (P2P) Network. The distributed hash table (DHT) layer and version control (VC) layer is the core of this framework. Software clients can carry out initializing and upgrading by the atomic operations of a version control. Borrowing from P2P, we weave the distributed hash table (DHT) algorithm to speed up the download rate of a version control so that this framework will not crash under the failure of a single node. Finally, experiments have showed the high performance and availability of the proposed framework.